TINDAK TUTUR DALAM WACANA BIMBINGAN PRANIKAH DI KANTOR URUSAN AGAMA (KUA) KABUPATEN BALANGAN - Junianti, Henny (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2019)
AbstractThis study focused on assertive speech acts, directive speech acts, commissive speechacts, expressive speech acts, and declarative speech acts used in pre-marital counselingdiscourse. This research is expected to provide a description of these speech acts. Thisresearch used a qualitative approach. The source of data in this study was the KUAofficials who gave pre-marital counseling in KUA of Balangan. The data collectiontechniques in this research were recording and note-taking. From the results of theresearch, it was concluded that there were five types from Searle of speech acts used ina pre-marital counseling, namely: (1) assertive speech acts in the forms of a)maintaining marriage, b) stating the purpose of marriage, marriage problems, theimportance of marriage certificates, understanding the Board of Advisory, abouthusband and wife, and c) reporting ages of marriage; (2) directive speech acts in theforms of a) suggestions to get married, resolving marriage problems, and formingharmonious marriage, b) asking for forming and fostering sakinah, mawadah,warahmah marriage, and worshiping Allah, c) asking couples for carrying out theduties and obligations as husband and wife, and d) recommending marriage, carryingout duties and obligations of husband, wives, and carrying out joint obligations; (3)commissive speech acts in the form of submitting proposals for a marriage contract; (4)expressive speech acts in the forms of a) thanking prospective brides and grooms, b)congratulating couples, c) regretting if the reasons for marriage, d) apologizing tomarried couples, and e) censuring married couples who did not apply mandi wajib andwives; and (5) declarative speech acts in the form of determining whether the marriagewould be held or not and deciding the marriage of the couples.Key words: speech acts, premarital guidance discourse61AbstrakPenelitian ini memfokuskan pada tindak tutur asertif, ekspresif, dan tindak tuturdeklaratif yang digunakan dalam wacana bimbingan pranikah. Penelitian inidiharapkan dapat memberikan deskripsi tentang tindak tutur tersebut. Penelitian inimenggunakan pendekatan kualitatif. Sumber data dalam penelitian ini adalah dalampetugas KUA yang memberikan bimbingan pranikah di KUA Kabupaten Balangan.Teknik pengumpulan data dalam penelitian ini ialah dengan teknik rekam dan teknikcatat. Dari hasil penelitian, dapat disimpulkan ada lima jenis tindak tutur menurutSearle yang digunakan dalam bimbingan pranikah, yakni: (1) tindak tutur asertifberupa a) mempertahankan rumah tangga, b) menyatakan tujuan menikah, masalahrumah tangga, pentingnya buku nikah, dan tentang suami istri, dan c) melaporkan usiamenikah; (2) tindak tutur direktif berupa a) menyuruh nikah/kawin, menyelesaikanpermasalahan rumah tangga, dan membentuk rumah tangga yang harmonis, b)memohon membentuk dan membina rumah tangga yang sakinah, mawadah, warahmah,dan beribadah kepada Allah Swt., c) menuntut melaksanakan tugas dan kewajibansuami, istri, dan syarat poligami, dan d) menyarankan menikah/kawin, melaksanakantugas dan kewajiban suami, istri, dan kewajiban bersama.; (3) tindak tutur komisifberupa mengajukan usulan melanjutkan, menunda, atau membatalkan akad nikah; (4)tindak tutur ekspresif berupa a) terima kasih pada calon pengantin, b) mengucapkanselamat menempuh hidup baru kepada pasangan pengantin, c) menyesalkan alasanpernikahan, d) permintaan maaf pada pasangan suami istri, dan e) mengecampasangan suami istri tidak melaksanakan mandi wajib dan suka berselisih.; dan (5)tindak tutur deklaratif berupa memutuskan akan berlangsungnyapernikahan/perkawinan dan memutuskan nikah/kawinnya pasangan pengantin.Kata-kata kunci: tindak tutur, wacana bimbingan pranikah